EFL teachers’ perceptions on professional development for language proficiency maintenance and improvement - Utami Widiati; Him’mawan Adi Nugroho; Ani Susanti (Institute of Advanced Engineering and Science, 2022)
This case study investigated the phenomenon of English as a foreign language (EFL) teachers’ perceptions of professional development (PD) related to language proficiency, which has become a critical issue in the field of EFL teaching and has played an important role in facilitating students to learn English well. Interview guides were employed as the main instrument to elicit information about PD activities related to language proficiency maintenance and improvement, comprising closed-ended and open-ended items. The participants of the study were six professional EFL teachers who have had 5 to 30 years of teaching experience, selected from high schools in a capital city in Indonesia. Data were analyzed descriptively to result in frequencies of importance levels and qualitatively to explore patterns of PD activities. The results showed that two factors affecting the participants’ acknowledgement of the importance of language proficiency PD activities: the need to maintain and improve language proficiency and the benefits of proficiency for teaching and learning. It is recommended that Indonesian EFL teachers develop self-awareness of the importance of improving their skills not only pedagogically but also professionally and realize that PD for language proficiency in particular is imperative to help them keep their professionalism high.